Gender Differences in Learning Outcomes from the College Experiences of Engineering Students. Issue 3 (5th July 2016) - Ro, Hyun Kyoung; Knight, David B.
Abstract: Background: Although prior studies have shown how female students' college experiences influence persistence, graduation, and career choice, we consider how specific college experiences may produce different learning outcomes for men and women in engineering programs. Purpose: This article explores how curricular emphases, instructional approaches, and co‐curricular participation affect learning outcomes differently by gender. Design/Method: This study used a nationally representative weighted survey sample of 4, 901 students in 120 Untied States engineering programs. We used a multilevel regression approach to test for the interaction effects between gender and college students' experiences on learning outcomes deemed critical for career success. Results: We identified the curricular emphases, instructional approaches, and co‐curricular participation that affected learning outcomes differently by gender. Greater curricular emphasis on professional skills and a greater frequency of student‐centered teaching led to greater self‐reported design skills for women. Being more active in nonengineering clubs increased female students' self‐reports of fundamental, design, and communication skills. Conclusions: The findings of this study support investigation of ideas that might help female students develop learning outcomes more effectively. Future research should consider applying our analytical approach to identify how college experiences affect different groups of students differently.